Measurable Residual Disease Response and Prognosis in Treatment-Naïve Acute Myeloid Leukemia With Venetoclax and Azacitidine. Issue 8 (10th March 2022) - Pratz, Keith W.; Jonas, Brian A.; Pullarkat, Vinod; Recher, Christian; Schuh, Andre C.; Thirman, Michael J.; Garcia, Jacqueline S.; DiNardo, Courtney D.; Vorobyev, Vladimir; Fracchiolla, Nicola S.; Yeh, Su-Peng; Jang, Jun Ho; et al.
Abstract : PURPOSE: There is limited evidence on the clinical utility of monitoring measurable residual disease (MRD) in patients with acute myeloid leukemia treated with lower-intensity therapy. Herein, we explored the outcomes of patients treated with venetoclax and azacitidine who achieved composite complete remission (CRc; complete remission + complete remission with incomplete hematologic recovery) and MRD < 10 –3 in the VIALE-A trial. METHODS: The patients included in this report were treated with venetoclax and azacitidine. Bone marrow aspirate samples for multiparametric flow cytometry assessments were collected for central analysis at baseline, end of cycle 1, and every three cycles thereafter. MRD-negative response was defined as < 1 residual blast per 1, 000 leukocytes (< 10 –3 or 0.1%) with an estimated analytic sensitivity of 0.0037%-0.0027%. CRc, duration of remission (DoR), event-free survival (EFS), and overall survival (OS) were assessed. A multivariate Cox regression analysis identified prognostic factors associated with OS. RESULTS: One hundred sixty-four of one hundred ninety (86%) patients with CRc were evaluable for MRD. MRD < 10 –3 was achieved by 67 of 164 (41%), and 97 of 164 (59%) had MRD ≥ 10 –3 . The median DoR, EFS, and OS were not reached in patients with CRc and MRD < 10 –3, and the 12-month estimates for DoR, EFS, and OS in this group were 81.2%, 83.2%, and 94.0%. Among patients with CRc and MRD ≥ 10 –3, the median DoR, EFS, and OS were 9.7, 10.6, and 18.7 months. Multivariate analysis showed that CRc with MRD < 10 –3 was a strong predictor of OS (adjusted hazard ratio = 0.285; 95% CI, 0.159 to 0.510; P < .001). CONCLUSION: Patients who achieved CRc and MRD < 10 –3 with venetoclax and azacitidine had longer DoR, EFS, and OS, than responding patients with MRD ≥ 10 –3 . Abstract :